From Local to Global: Transformation of the Indonesian Civil Service through Public Administration Reform - Hutahaean, Marlan (Iapa Proceedings Conference, 2024)
Public administration reform is the Indonesian government's strategy to increase the capacity of the Indonesian Civil Service (ICS) to be able to compete at the global level. This article reveals the approach that has been taken so far and the development model for increasing ICS capacity so that they are able to compete globally. The main problem with Indonesian ICS is the lack of ability to compete internationally, especially ICS in local government. In fact, for a region to progress, one of the requirements is that its ICS competency must be qualified, not only local, but global. By using a descriptive qualitative approach, researchers found that the public administration reforms carried out so far in Indonesia are more about bureaucratic reform. Public administration reform is very broad, covering various dimensions. Bureaucracy is only one of the various dimensions of public administration that exist, such as public policy, public management, public organizations, public ethics, public environment, and performance. For this reason, it is necessary to reform public administration as a whole, through the development of a model that is able to increase the competence of Indonesian ICS at international standards.